Season‐long characterization of high‐cannabinoid hemp (Cannabis sativa L.) reveals variation in cannabinoid accumulation, flowering time, and disease resistance. Issue 4 (21st January 2021) - Stack, George M.; Toth, Jacob A.; Carlson, Craig H.; Cala, Ali R.; Marrero‐González, Mariana I.; Wilk, Rebecca L.; Gentner, Deanna R.; Crawford, Jamie L.; Philippe, Glenn; Rose, Jocelyn K. C.; Viands, Donald R.; Smart, Christine D.; et al.
Abstract: Given the dramatic rise in high‐cannabinoid hemp ( Cannabis sativa L.) production in the last decade, there is an increasingly urgent need to characterize available germplasm and develop knowledge to accelerate the breeding of uniform and stable cultivars. Despite persistent cultivation of hemp cultivars for grain and or fiber around the world, the diversity and genetic underpinning of key traits for breeding and cultivation are poorly understood. For 30 high‐cannabidiol hemp cultivars replicated on two field sites, we sought to evaluate yield, agronomic performance, and disease resistance while also conducting a detailed study of cannabinoid accumulation over the course of floral maturation. We observed significant variation in both within and among cultivars. During the growing season, the plants clustered into five groups by growth rate and varied in flowering time from photoperiod insensitive to photoperiod sensitive with very short critical photoperiods. Based on the observed ratio of total potential cannabidiol (CBD) to total potential tetrahydrocannabinol (THC), there was segregation for cannabinoid chemotype in some seeded cultivar populations. Analysis of cannabichromene (CBC) production revealed that some cultivars had a discretely lower CBD:CBC ratio than the others. There was a continuous range of powdery mildew severity by cultivar, with one that had little to no observed powdery mildew suggesting it might have genetic resistance. Biomass production at harvest was strongly influenced by location and cultivar, and there was variation by cultivar in the relative cannabinoid production in shoot tip samples compared with whole plant samples. While our results provide preliminary guidance regarding relative performance of current cultivars, our analyses indicate a need for additional hemp breeding to provide stable, uniform, and legally compliant cultivars with improved disease resistance and flowering times optimized for the latitudes of different growing locations. Abstract : There is an increasingly urgent need to evaluate hemp cultivars, especially those selected for cannabinoid production, and develop knowledge to accelerate the breeding of uniform and stable cultivars. This paper describes extensive characterization of 30 high‐cannabinoid hemp cultivars replicated on two sites. We describe variation for growth, flowering time, and cannabinoid production that will inform breeding programs and cultivar selection.